Citizens' intention to invest in municipal solid waste to energy projects in Ghana: The impact of direct and indirect effects. (1st September 2022) - Nketiah, Emmanuel; Song, Huaming; Cai, Xiang; Adjei, Mavis; Adu-Gyamfi, Gibbson; Obuobi, Bright
Abstract: Growing industry, urbanization, and population in developing nations like Ghana is increasing waste generation. Municipal solid waste (MSW) mishandling has serious environmental, public health, and socio-economic implications. This study analyzed the direct and indirect influence on citizens' intention to invest in MSW to energy projects in Ghana and expanded the norm activation model (NAM) and theory of planned behavior (TPB) with perceived value and health consciousness. With 412 questionnaire responses, hypothetical statements were evaluated using partial least square-structural equation modeling (PLS-SEM). The findings are: (1) The study found that awareness of consequences indirectly influenced citizens' intention to invest in MSW to energy projects through attitude, personal norms, perceived value, perceived behavioral control, subjective norm, and health consciousness. (2) This study indicated that the explanatory ability of the current structural research model (R 2 = 40.1%) is better than that of the extended TPB model (R 2 = 38.0%) and NAM (R 2 = 28.4%) with perceived value and health consciousness, and the structural model can better explain their intention to invest. Additionally, several recommendations are suggested for investing in MSW to energy projects in Ghana. This study has the potential to assist academics, researchers, government officials, and investors engaged in MSW to energy projects in making knowledgeable decisions. Highlights: Citizens' intention to invest in MSW to energy projects was assessed in Ghana. The study assessed the explanatory power of TPB and NAM using PLS-SEM. All the hypothesis influenced citizens' intention to invest in the projects. The study compare the current research model, NAM, and the TPB model. The recommendations for citizens' intention to invest in the projects are detailed.